Development of Students’ Worksheets Based on Problem-Based Instruction (PBI) of Grade X Senior High School - Elvira Diana. S; I Made Arnawa; Ratnawulan Ratnawulan (Postgraduate School, Universitas Negeri Padang, 2020)
This study is intended to produce senior high school students' mathematical worksheets based on valid, practical and effective problem-based instruction. Its effectiveness can be seen from the increase in positive activity and student learning outcomes. It is research and development by using the Plomp model by using three stages, namely the preliminary research, development or prototype phase, and assessment phase. The subjects were students of class X SMAN 1 Lembah Gumanti. The research instruments were interview guidelines, field notes, validation sheets, student and teacher response questionnaires, students’ activity observation sheets and learning achievement tests. This research has produced students’ worksheets that are valid, practical and effective. Students and teachers give a good response of students’ worksheet because it helps them in the learning process. Students can learn efficiently and understand the mathematical concepts easily. Students’ worksheet can also motivate students in learning so that there is enhancement between positive activities and learning outcomes.